Usulan Penilaian Daya Dukung Pariwisata Pada Ekowisata Geopark CiletuhPalabuhanratu, Kabupaten Sukabumi, Jawa Barat - Sabila, Najaah; Azaria, Irenne (JURNAL DESTINASI PARIWISATA; Vol 12 No 1 (2024): VOL 12, NO 1 (2024): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2024)
The surge in visitor numbers to nature-based tourist areas, especially protected areas, has led to a decline in environmental quality and created a public discomfort in travel experiences. This circumstance underscores the necessity for management efforts through the application of the Tourism Carrying Capacity (TCC) concept. While the TCC concept has been successfully applied in various natural sites such as caves, coastal areas, and natural forests, its application in geological sites has been less explored. One such geological site in Indonesia recognized by UNESCO is the Ciletuh-Palabuhanratu Geopark, Sukabumi Regency, West Java. This study aims to apply a TCC assessment framework to the geological site of the Ciletuh Geopark. The chosen method for this study involves a literature review approach. The results indicate that the proposed TCC assessment framework can be applied to the Ciletuh Geopark through system analysis, determination of management priorities, and TCC calculations. Nevertheless, the design faces challenges in terms of the time required for preparation and substantial funding. TCC assessment also relies on system analysis and researcher interpretations, necessitating regular discussions and evaluations involving all stakeholders to achieve an accurate and targeted TCC assessment. Keywords: Ciletuh Geopark, Ecotourism, Geoconservation, Tourism, TCC